Increasing Performance Treatment Index’s Score (PTI) of Elementary School Children in Keputih-Surabaya Through Dental Public Health Warrior Project - Aulia Dwi Maharani (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2017)
Introduction:The Dental Public Health Warrior (DPHW) project is a social activity which provides a creative, fun, and interactive dental health education throughout elementary schools in Keputih Area-Surabaya,Indonesia. Purpose: The aim of this study was to determine the effectivity of those projects in increasing the Performance Treatment Index of elementary school’s student. PTI score used to measure the willingness to treat their teeth. Materials and Methods:In this pre experimental study (pretest and posttest only design), subjects were 54 elementary students (4th grade) . All subjects were educated by the DPHW team and their DMF-t score and PTI score were collected by calibrated dentists before the education and in 3 months after the education. Results: The mean of DMF-t score increase from 6,7 to 6,9. The mean of PTI score increase from 3,7 to 9,5 . Wilcoxon analysis showed there is significant different between before and after education (p= 0,001). Conclusion:. The DPHW project can be effectively used to increase the Performance Treatment Index of elementary school’s student. The increase of PTI indekx means there is increase in willingness to treat their teeth.